INVESTIGATION ON SURFACE, ELECTRICAL AND OPTICAL PROPERTIES OF ITO-AG-ITO COATED GLASS - (:unkn) unknown (KHARKOV INST PHYSICS & TECHNOLOGY, 2015)
The aim of this work was to study the optical and electrical properties of thick ITO-Ag-ITO multilayer coating onto glass. ITO-Ag-ITO coatings with thickness of ITO layers 110 nm, 185 nm and intermediate Ag layer thickness 40 nm were prepared by magnetron sputtering. The optical, electrical and atomic properties of the coating were examined by scanning electron microscope, atomic force microscope, X-ray diffraction analysis and ultraviolet-visible spectroscopy.